Fecal microbiota transplant as treatment for recurrent urinary tract infections: a proof-of-concept study - Rico-Caballero, Verónica; Romero-Rivera, Mario; Moreno-Blanco, Ana; Aira, Andrea; Casals-Pascual, Climent; Rodríguez-Jiménez, Concepción; Quereda, Carmen; Soriano, Alex; Del Campo, Rosa (Springer, 2025)
Recurrent urinary tract infections (rUTIs) are a global problem due to their high prevalence and because are caused by antibiotic-resistant strains. The hypothesis of our study is that a fecal microbiota transplant (FMT) might reduce the pres ence of uropathogenic E. coli in the intestinal microbiota, thereby leading to a decrease in the rUTIs. The objective of this study was to assess the efficacy of a single FMT intervention for the treatment rUTIs. A total of 22 postmenopausal women received a 3-day course of oral rifaximin to reduce their commensal microbiota, followed by a 2-day washout period, and then an oral FMT using lyophilized fecal capsules equivalent to 100 g of freeze-dried fecal matter from a single cer tificated fecal donor. The results demonstrated that over a period of six months, there was a 68.1% reduction in urinary infectious episodes, with minimal adverse effects. In addition, eradication of fecal colonization of urinary pathogens that were resistant to multiple antibiotics was achieved. The findings of this pilot study indicate that FMT is a promising and safe alternative for the treatment of rUTIs, particularly those caused by multidrug-resistant bacteria.